Vascular Function Is Improved After an Environmental Enrichment Program: The Train the Brain–Mind the Vessel Study. Issue 6 (June 2018) - Bruno, Rosa Maria; Stea, Francesco; Sicari, Rosa; Ghiadoni, Lorenzo; Taddei, Stefano; Ungar, Andrea; Bonuccelli, Ubaldo; Tognoni, Gloria; Cintoli, Simona; Del Turco, Serena; Sbrana, Silverio; Gargani, Luna; et al.
Abstract : Environmental enrichment may slow cognitive decay possibly acting through an improvement in vascular function. Aim of the study was to assess the effects of a 7-month cognitive, social, and physical training program on cognitive and vascular function in patients with mild cognitive impairment. In a single-center, randomized, parallel-group study, 113 patients (age, 65–89 years) were randomized to multidomain training (n=55) or usual care (n=58). All participants underwent neuropsychological tests and vascular evaluation, including brachial artery flow-mediated dilation, carotid–femoral pulse wave velocity, carotid distensibility, and assessment of circulating hematopoietic CD34+ and endothelial progenitor cells. At study entry, an age-matched control group (n=45) was also studied. Compared with controls, patients had at study entry a reduced flow-mediated dilation (2.97±2.14% versus 3.73±2.06%; P =0.03) and hyperemic stimulus (shear rate area under the curve, 19.1±15.7 versus 25.7±15.1×10 −3 ; P =0.009); only the latter remained significant after adjustment for confounders ( P =0.03). Training improved Alzheimer disease assessment scale cognitive (training, 14.0±4.8 to 13.1±5.5; nontraining, 12.1±3.9 to 13.2±4.8; P for interaction visit×training=0.02), flow-mediated dilation (2.82±2.19% to 3.40±1.81%, 3.05±2.08% to 2.24±1.59%; P =0.006; P =0.023 after adjustment for diameter and shear rate area under the curve), and circulating hematopoietic CD34 + cells and prevented the decline in carotid distensibility (18.4±5.3 to 20.0±6.6, 23.9±11.0 to 19.5±7.1 Pa −1 ; P =0.005). The only clinical predictor of improvement of cognitive function after training was established hypertension. There was no correlation between changes in measures of cognitive and vascular function. In conclusion, a multidomain training program slows cognitive decline, especially in hypertensive individuals. This effect is accompanied by improved systemic endothelial function, mobilization of progenitor CD34 + cells, and preserved carotid distensibility. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01725178. Abstract : Supplemental Digital Content is available in the text.